Ocupações irregulares às margens da Rodovia BR 287 em Santa Maria/RS - Pilar, Adriana Medianeira Rodrigues (2009)
The accelerated urban expansion that occurs with the city of Santa Maria/RS is also connected with the intense process of irregular occupation of its perimeter urban. Known as the "city of intrusion," Santa Maria has experienced, particularly in the last ten years, mass occupation of motorway BR 287 margins with four occupations, and three of them within the West and South-West. The craving for housing worthy according to your profile cost-effective comes bringing hundreds of people to occupy public domain areas unsuitable for housing facility. However, the ease of access to goods and services does, in many cases, the risk condition awareness of those people who created an identity with the place where they live for more than five years. Victims often speculation popular public areas, there are cases themselves residents ultimately becomes estate agents acting on the sale of real estate irregular profiting from the appreciation of these areas through access to equipment condition of neighbouring districts and the conquest of new which is thus also diversified trade training in these occupations. On the other hand, there are those individuals that the real purpose boils intrinsically in the conquest, aware that they are installed in the areas of risk. Are people that unemployment and/or underemployment the renders payment of rent and awaiting tirelessly for a solution of the public. Currently, the programme for accelerated growth of the Federal Government has made possible the realization of housing programmes for a range of income until a minimum wage and has provided the process of relocation of many families in areas at risk in Santa Maria/RS. Covered with one of the city's residential programs, residents of the occupation on the fringes of BR 287 of neighborhood Urlândia relocated in March 2009 for villas of 40,12 m² in blending Cipriano da Rocha, in. But as for occupations on the fringes of road in the West there is a consensus of the public authorities in relocate residents. The deadlock condition property is one of the major snags along the great demand homeless worthy who owns the city of Santa Maria, without counting the great strength of residents of Santa Marta that speculation is very strong. We need public housing policies covering a dignified housing condition that consider the size of families, their socio-economic conditions and, finally, grant the right to the city.